Students’ Perception of Using Podcasts to Improve Listening Skill - Anisah Anisah; Ziad Muhammad; Chairina Nasir (English Education Journal: Jurnal Pengembangan Pendidikan dan Pengembangan Pengajaran Bahasa, 2025)
This study examines students’ perceptions of using podcasts as a tool to improve their listening skills while learning English. The aim of the research is to examine how students view English podcasts and to find out which types of podcasts are most preferred by students to improve their listening skills. The study was conducted among English students at Universitas Syiah Kuala and focused on the class of 2021. The research methodology included collecting data through surveys and analyzing students’ preferences and usage patterns of podcasts. The results show that students perceive podcasts as a useful medium for improving listening comprehension due to their accessibility and the variety of content available. The study also highlights the types of podcasts that the students preferred most for language learning. The researchers found three types of podcasts that students think have more impact on their learning: 82.27% for the interview type, followed by the storytelling type with a score of 81.36% and the third favorite type of podcast is the conversation podcast with a score of 80.45%. These three podcast types are the most preferred podcasts for students in improving their listening skills, which could inform future educational practices and curriculum development. This research contributes to the growing body of knowledge related to integrating digital media in language learning and offers educators practical insights into using podcasts in improving listening skills.